2013
DOI: 10.1073/pnas.1222327110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of parameters through which surface chemistry determines the lifetimes of hot electrons in small Au nanoparticles

Abstract: This paper describes measurements of the dynamics of hot electron cooling in photoexcited gold nanoparticles (Au NPs) with diameters of ∼3.5 nm, and passivated with either a hexadecylamine or hexadecanethiolate adlayer, using ultrafast transient absorption spectroscopy. Fits of these dynamics with temperature-dependent Mie theory reveal that both the electronic heat capacity and the electron-phonon coupling constant are larger for the thiolated NPs than for the aminated NPs, by 40% and 30%, respectively. Densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 49 publications
4
94
0
Order By: Relevance
“…These charge carriers are sufficient in quantity and lifetime to initiate external chemical processes [152]. The hot carriers further dephase through an additional relaxation mechanism consisting of electron-phonon interactions over 1-10 ps [154,155]. During these two time intervals, the charge carriers may contain sufficient energy to transfer to a nearby chemical species to initiate a single or multistep chemical reaction.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…These charge carriers are sufficient in quantity and lifetime to initiate external chemical processes [152]. The hot carriers further dephase through an additional relaxation mechanism consisting of electron-phonon interactions over 1-10 ps [154,155]. During these two time intervals, the charge carriers may contain sufficient energy to transfer to a nearby chemical species to initiate a single or multistep chemical reaction.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Thus, it will be useful to understand the extent to which the electronic properties of the core are dependent upon the nature of the ligand sphere. Prior experimental work on AuNPs has only demonstrated that gross changes in the ligand head group that binds to gold (amine versus thiolate: effectively testing the difference between physisorbed and chemisorbed ligands) can alter the surface plasmon resonance (SPR), electron–phonon coupling, or magnetic properties 2b. 4 In contrast, the effects of more subtle changes to ligand structure (e.g.…”
Section: Diameter Cesr Data and Spr Of C6 And C6/br Aunpsmentioning
confidence: 99%
“…1112 A central question that still remains and is critical for the further improvement in plasmon-assisted photo-catalytic processes is how charge transfer from the metal nanoparticle can effectively compete with the intrinsic ultrafast energy relaxation in the metal. 1316 …”
mentioning
confidence: 99%